Treatment with Ceftriaxone in Complicated Diverticulitis Increases the Incidence of Intra-Abdominal Enterococcus faecium Detection - Pochhammer, Julius; Kramer, Axel; Orth, Matthias; Schäffer, Michael; Beckmann, Jan Henrik (Surgical infections, 2021)
Background: Complicated diverticulitis of the sigmoid colon typically is treated by resection after initial antibiotic treatment. Third-generation cephalosporins are the drugs of choice but are not effective against enterococci and can induce colonic colonization by Enterococcus faecium within hours. Infections caused by enterococci, especially E. faecium, are difficult to treat but should be considered in the strategic treatment planning of hospital-acquired peritonitis (e.g., anastomotic leakage), especially in immunocompromised patients. - Methods: To determine whether the duration of pre-operative ceftriaxone treatment in complicated diverticulitis increases the incidence of intra-abdominal E. faecium detection, we analyzed all patients operated on for diverticulitis of the sigmoid colon in our department between 2008 and 2016. - Results: Analyzing 516 resections performed for complicated diverticulitis, we found that E. faecium generally was detected intra-abdominally more often in the group that underwent longer pre-operative ceftriaxone treatment (≥ 4 days). During primary resection, E. faecium was detected in 2.7%, 11.1%, and 37.0% cases in the group undergoing immediate operation, 1-3 days of antibiotic treatment, and ≥4 days of antibiotic treatment, respectively. Enterococcus faecium was detected in 0, 25.0%, and 70.6% of surgical revisions and 28.6%, 14.3%, and 56.0%, respectively, of incisional surgical site infections with identified pathogens. A multivariable analysis discovered anastomotic leakage and antibiotic treatment lasting ≥4 days to be independent risk factors for intra-abdominal isolation of E. faecium. - Conclusion: A ceftriaxone treatment ≥4 days led to a higher incidence of intra-abdominal E. faecium. Our data further suggested that empiric coverage of E. faecium in the treatment of hospital-acquired peritonitis could be beneficial after a long duration of ceftriaxone treatment.
Gesehen am 12.08.2024